Antimicrobial Activity of Extracts of "Hairy" Root Culture and Regenerated Plants of Ruta graveolens L. Against Some Soil and Pathogenic Bacteria - Bielikova, Оlena; Matvieieva, Nadiia; Tashyrev, Oleksandr; Yastremskaya, Larisa (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Ruta graveolens L. has potential value in traditional medicine by various active substances in the composition, which act as antioxidants and have anticancer, antiviral and antibacterial properties. The present study was undertaken to evaluate the effect of genetic transformation on antibacterial activity of ethanol and water extracts of “hairy” root culture and regenerated plant of Ruta graveolens against human pathogenic bacteria Staphylococcus aureus B-904, Bacillus subtilis sub sp. subtilis, Escherichia coli В-906, Pseudomonas aeruginosa В-907 and soil bacteria Micrococcus luteus, Enterobacter hormaechei, Kocuria carniphila, Citrobacter freundii, Rhodococcus erythropolis and yeast Saccharomyces.cerevisiae, Candida tropicalis. Both extracts from control and transgenic roots demonstrated antimicrobial activity against Gram-positive bacteria. The extracts didn’t inhibit growth of Gram-negative bacteria and yeast. The activity of ethanol extract was greater than the activity of water extracts. In some cases, the extracts from ‘hairy” root culture exhibited higher antimicrobial activity than the extracts from the control plants.